Self-healing mortar using different types, content, and concentrations of bacteria to repair cracks. - Mohamed Ahmed Refat El-Mahdy; Ahmed ELShami; Mohamed Yousry Elshikh; Seleem Saleh Elsayed Ahmad (Fracture and Structural Integrity)
The creation of cracks, which are the most common cause of structural failure, has a significant impact on the structure's strength and durability. As a result, effective repair and maintenance are vital and unavoidable for treating any of these issues. Self-healing mortar holds promising benefits for reducing the cost of repair as cracks are autonomously repaired without any human intervention. This study investigated the effect of bacteria type, bacteria content, bacteria concentration, and nutrient type on the properties of the self-healing mortar. Three types of bacteria, Bacillus sphaericus, Bacillus Megaterium, and Bacillus subtilis encapsulated in calcium alginate beads, were introduced into the mortar. Two concentrations of bacteria, 2× 108 and   2× 109 Colony Forming Units per milliliter, and different percentages of bacteria of cement weight were selected for the study. In addition, calcium lactate and calcium acetate were used at 0.5% of cement weight as nutrition for bacteria. Tests were performed for compressive strength, bending strength, SEM, EDX, and TGA/DTG. The results show a significant development in the mechanical behaviour of mortar, especially with Bacillus Megaterium using a 2.5% bacterial proportion with a concentration 2× 109 CFU/ml. This can be related to the filling of voids and cracks in microbial mortar by calcite, which was confirmed by SEM and EDX.